Activation of NF-κB induced by TRIMCyp showing a discrepancy between owl monkey and northern pig-tailed macaque. (September 2018) - Zhu, Jia-Wu; Mu, Dan; Liu, Feng-Liang; Luo, Meng-Ting; Luo, Rong-Hua; Zheng, Yong-Tang
Highlights: omTRIMCyp induces NF-κB activation in a dose-dependent, but npmTRIMCyp does not. Both omTRIMCyp and npmTRIMCyp can promote AP-1 and IFN-β activation. CypA domain of omTRIMCyp plays an important role in NF-κB activation. omTRIMCyp enhances IκBα and IRF3 phosphorylation, but npmTRIMCyp does not. Abstract: TRIMCyp generated by retrotransposition of a cyclophilin A inserting into TRIM5 locus, has been identified in owl monkey and most of Old World monkeys (OWM). Owl monkey TRIMCyp (omTRIMCyp) inhibits HIV-1 infection by direct interaction with viral capsid and indirect innate immune induction, whereas most of TRIMCyps from OWM cannot inhibit HIV-1, and the impact of which on immunoregulation is largely unknown. Here we reported that omTRIMCyp induces NF-κB, AP-1 and IFN-β activation in a dose-dependent manner, while TRIMCyp from northern pig-tailed macaque (npmTRIMCyp) does not activate NF-κB and moderately enhances AP-1 and IFN-β activities. The Cyclophilin A (CypA) domain plays an important role in omTRIMCyp-mediated NF-κB activation, and RBCC domains have a synergetic effect. We further indicated the mechanism by which npmTRIMCyp unable to activate NF-κB is that npmTRIMCyp hardly phosphorylates IκBα, different from omTRIMCyp which dramatically induces IκBα phosphorylation. Ubiquitination activity of omTRIMCyp was greater than npmTRIMCyp, although both could be ubiquitylated. Given that npmTRIMCyp neither interacts with viral capsid resulting in susceptibility to HIV-1 infection, nor activates NF-κB that is indispensable to HIV-1 provirus transcription, we proposed a model that npmTRIMCyp may play an important role in HIV-1 infected northern pig-tailed macaque with latency.